Updates in Diagnosis and Management of CSF Rhinorrhea: A Systematic Review - Maali Subhi T Alshammari; Ghadah Khalid H. Alanazi; Taif Khalaf K. Alanazi; Reef Ayed R. Alshammari; Wasan Ghathwan A Alanazi; Madhawi Abdulaziz Alanazi; Dhaidan Mohsen Alshammari; Ikechukwu Odeh Odeh (The Bioscan, 2024)
Objectives: To synthesize current evidence on the diagnosis and management of cerebrospinal fluid rhinorrhea (CSFR). Methods: A thorough search of pertinent databases following the PRISMA guidelines was done in order to find studies that satisfied the requirements for inclusion. A thorough search of PubMed, Web of Science, SCOPUS, and Science Direct was conducted to find pertinent literature. Results: Eleven studies, including a total of 382 CSFR patients and 170 (44.5%) of them were males, were included in our data. The success rate of the trans-nasal endoscopic approach ranged from 66.6% to 100%, while Endoscopic endonasal eustachian tube obliteration (EEETO) reported a success rate of 65.1%. Meningitis, pneumocephalus, frontal Sinusitis, failure of closure (immediate), and failure of closure (delayed) were the reported adverse effects following trans-nasal endoscopy in CSFR. No adverse effects were reported among patients who underwent EEEO. 0.06% ipratropium bromide nasal spray reaction was useful in excluding CSFR, and computed tomography cisternography (CTC) and magnetic resonance hydrography (MRH) had excellent sensitivity for CSFR diagnosis. Conclusion: The preferred and most reported technique for repairing CSF fistulae in the majority of clinical situations is now endoscopic surgery with success rates ranged from 66.6% to 100%. CSFR is a general diagnostic that encompasses several locales and etiologies.